The angel and the three man: quran stories for little hearts - Khan, Saniyasnain (GoodwordKidz New Delhi, 2004)
This tale describes an encounter between an angel and three men who are tested in their faith and character. It illustrates themes of morality, accountability, and the importance of righteous actions.